Puberty, sex, and fear extinction retention: A neuroimaging study in youth - Sneha Bhargava; Clara G. Zundel; MacKenna Shampine; Samantha Ely; Carmen Carpenter; Jennifer Losiowski; Shravya Chanamolu; Jovan Jande; Reem Tamimi; Kamakashi Sharma; Emilie O’Mara; Alaina M. Jaster; et al. (Developmental Cognitive Neuroscience, 2025)
Anxiety disorders affect 31.1 % of U.S. adults, with females exhibiting twice the prevalence of males. While sex differences are well-documented, underlying mechanisms remain unclear. Advanced pubertal status is linked to increased anxiety symptoms in females but not males, suggesting puberty contributes to sex differences in fear-based disorders. Deficits in fear extinction and retention are implicated in anxiety, and prior research suggests sex hormones influence extinction retention. This study examined sex assigned at birth (parent-reported) and pubertal status (self-reported) on extinction retention in 101 youth (47.5 % female) using a Pavlovian fear extinction paradigm. Measures included self-reported anxiety symptoms, extinction retention, and neural activation in the amygdala, hippocampus, and anterior cingulate cortex (ACC).